Sustained passing performance of elite and subelite female soccer players following a female match-specific exercise protocol - Lyons, M. J.; Conlon, J.; Perejmibida, A.; Chivers, P.; Joyce, C. (International Journal of Sports Physiology and Performance, 2021)
Purpose: This study examined the maintenance of passing performance following soccer-specific high-intensity intermittent exercise in elite (n = 9) and subelite (n = 11) Western Australian female soccer players (19.5 [2.5] y). Methods: A total of 20 participants completed the Loughborough Soccer Passing Test (LSPT) prior to, during, and following 90 minutes of a modified, female-specific, individualized exercise protocol (Loughborough Intermittent Shuttle Test [LIST]) to simulate 2 halves of a soccer match. Performance in the LSPT was calculated by adding "raw time" to the accumulated "penalty time" for each test. Results: Elite players recorded greater distances (t 58 = 4.671, P < .001, effect size [ES] = 1.21) and higher derived VO2max values (t 58 = 4.715, P < .001, ES = 1.20) for the LIST exercise protocol over the subelite players. The total performance times for each LSPT were longer in the subelites in comparison with the elites, with a very large ES difference seen in post-LIST1 (t 18 = -6.64, P < .001, ES = 2.99) and post-LIST2 (t 18 = -9.143, P < .001, ES = 4.12). No between-groups differences were identified for "raw time" at any time point. Hence, all reported LSPT performance differences are attributed to "penalty time." Conclusion: These data suggest that elite players can sustain their passing performance more efficiently throughout match play that can subelite female soccer players. These findings may contribute to future talent-identification testing by helping to distinguish between elite- and subelite-level players through sustained passing performance. Coaches may also use this information to better inform best-practice training methods through modification of male soccer-specific high-intensity intermittent exercise to a female cohort.